Effect of chemotherapy on the histological appearances of testicular teratoma metastatic to the lung: correlation with patient survival. - Madden, M (1984)
We report on 20 patients with teratoma of the testis metastatic to the lungs who underwent surgical enucleation of the pulmonary metastases. Seven patients showed predominantly undifferentiated tumour in the pulmonary metastases; six of these died within 26 months, while the seventh was lost to follow up. Four patients showed only scarring or total necrosis of their pulmonary lesions. These patients all received full courses of chemotherapy before surgery and are alive and well with no evidence of recurrence up to four years after diagnosis. In nine patients the pulmonary nodules consisted entirely of well differentiated tissues of benign appearance, sometimes resembling primary pulmonary adenochondromas. These patients also received full courses of chemotherapy before surgery; one died of disseminated disease but the other eight are all alive and well with survival intervals of up to 14 years after presentation. These findings show that following chemotherapy, necrosis and differentiation of teratomatous pulmonary metastases signify a good prognosis.